Industrial Democracy in Western Europe: A North American Perspective - Crispo, John H. G. (McGraw-Hill Ryerson, 1978)
John Crispo reviews the latest trends in industrial democracy in Western Europe. The book is based upon his earlier work in this area and a recently completed 10-month tour of the countries involved, which he spent interviewing labour and management representatives and other interested individuals throughout Western Europe. The result is an up-to-date and comparative account of the dynamic field of industrial democracy, which is defined to embrace union and worker influence in decision-making in all levels of society. Although the book focuses on Western Europe, it has been written in a manner to highlight the relevance of what is taking place there for industrial relations in North America. –Publisher's description
Keywords: Collective bargaining – Europe

The Canadian Industrial Relations System - Crispo, John H. G. (McGraw-Hill Ryerson, 1978)
Textbook on the system of labour relations in Canada - covers the nature of Canada's constitutional and legal system, the role of employers organizations, trade unions and employees associations, the labour movement (including Its history), collective bargaining and inflation, and comments on standards of labour legislation, labour disputes and dispute settlement, [and] future trends. Flow charts and references. –Google Books description
Keywords: Industrial relations – Canada